The ALK inhibitor PF-06463922 is effective as a single agent in neuroblastoma driven by expression of ALK and MYCN - J. Guan; E. R. Tucker; H. Wan; D. Chand; L. S. Danielson; K. Ruuth; A. El Wakil; B. Witek; Y. Jamin; G. Umapathy; S. P. Robinson; T. W. Johnson; et al. (The Company of Biologists, 2016)
The first-in-class inhibitor of ALK, c-MET and ROS1, crizotinib (Xalkori), has shown remarkable clinical efficacy in treatment of ALK-positive non-small cell lung cancer. However, in neuroblastoma, activating mutations in the ALK kinase domain are typically refractory to crizotinib treatment, highlighting the need for more potent inhibitors. The next-generation ALK inhibitor PF-06463922 is predicted to exhibit increased affinity for ALK mutants prevalent in neuroblastoma. We examined PF-06463922 activity in ALK-driven neuroblastoma models in vitro and in vivo. In vitro kinase assays and cell-based experiments examining ALK mutations of increasing potency show that PF-06463922 is an effective inhibitor of ALK with greater activity towards ALK neuroblastoma mutants. In contrast to crizotinib, single agent administration of PF-06463922 caused dramatic tumor inhibition in both subcutaneous and orthotopic xenografts as well as a mouse model of high-risk neuroblastoma driven by Th-ALKF1174L/MYCN. Taken together, our results suggest PF-06463922 is a potent inhibitor of crizotinib-resistant ALK mutations, and highlights an important new treatment option for neuroblastoma patients.